Why we fight [videorecording (DVD)] - Jarecki, Eugene; McCain, John, 1936-2018; Vidal, Gore, 1925-2012; Eisenhower, John S. D., 1922-2013 (Sony Pictures Home Entertainment, 2006)
Explores a half-century of U.S. foreign policy from World War II to the Iraq War, revealing how, as Dwight Eisenhower had warned in his 1961 Farewell Address, political and corporate interests have become alarmingly entangled in the business of war. On a deeper level, what emerges is a portrait of a nation in transition--drifting dangerously far from her founding principles toward a more imperial and uncertain future.